The Effect Of Work Discipline And Work Motivation On Employee Performance At Pt Infinit Teknika Industri - Daffa, Mahran; Utama, Rony Edward (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to test and analyze the Influence of Work Discipline and Work Motivation on Employee Performance at PT. Infinit Teknika Industri. The independent variables used are Work Discipline and Work Motivation, while the dependent variable is Employee Performance. The data collection method in this study was carried out by distributing questionnaires to 45 employees of PT. Infinit Teknika Industri. The research method used is quantitative which is associative using primary data. The results of this study indicate that Work Discipline has a positive and significant effect on Employee Performance with a calculated t value greater than t table 2.242 1.681 and a significant value of 0.03 1.681 and a significant value of 0.00 3.220) and a significant value of 0.00 0.05.